Effect of TB/HIV Integration on TB and HIV Indicators in Rural Ugandan Health Facilities. (15th December 2018) - Burnett, Sarah M.; Zawedde-Muyanja, Stella; Hermans, Sabine M.; Weaver, Marcia R.; Colebunders, Robert; Manabe, Yukari C.
Abstract : Background: The World Health Organization recommends integrating services for patients coinfected with tuberculosis (TB) and HIV. We assessed the effect of TB/HIV integration on antiretroviral therapy (ART) initiation and TB treatment outcomes among TB/HIV-coinfected patients using data collected from 14 rural health facilities during 2 previous TB and HIV quality of care studies. Methods: A facility was considered to have integrated TB/HIV services if patients with TB/HIV had combined treatment for both illnesses by 1 provider or care team at 1 treatment location. We analyzed the effect of integration by conducting a cross-sectional analysis of integrated and nonintegrated facility periods comparing performance on ART initiation and TB treatment outcomes. We conducted logistic regression, with the patient as the unit of analysis, controlling for other intervention effects, adjusting for age and sex, and clustering by health facility. Results: From January 2012 to June 2014, 996 patients with TB were registered, 97% were tested for HIV, and 404 (42%) were HIV-positive. Excluding transfers, 296 patients were eligible for analysis with 117 and 179 from nonintegrated and integrated periods, respectively. Being treated in a facility with TB/HIV integration was associated with lower mortality [adjusted odds ratio (aOR) = 0.38, 95% confidence interval (CI): 0.18 to 0.77], but there was no difference in the proportion initiating ART (aOR = 1.34, 95% CI: 0.40 to 4.47), with TB treatment success (aOR = 1.43, 95% CI: 0.73 to 2.82), lost to follow-up (aOR = 1.64, 95% CI: 0.53 to 5.04), or failure (aOR = 1.21, 95% CI: 0.34 to 4.32). Conclusions: TB/HIV service integration was associated with lower mortality during TB treatment even in settings with suboptimal proportions of patients completing TB treatment and starting on ART. Abstract : Supplemental Digital Content is Available in the Text.